Non-target Effects of Hyperthermostable α-Amylase Transgenic Nicotiana tabacum in the Laboratory and the Field - Ian Melville Scott; Hong Zhu; Katherine Schieck; Amanda Follick; L. Bruce Reynolds; Rima Menassa (Frontiers in Plant Science, 2019)
Thermostable α-amylases are important enzymes used in many industrial processes. The expression of recombinant Pyrococcus furiosus α-amylase (PFA) in Nicotiana tabacum has led to the accumulation of high levels of recombinant protein in transgenic plants. The initial steps to registering the transgenic tobacco at a commercial production scale and growing it in the field requires a risk assessment of potential non-target effects. The objective of this study was to assess the effect of feeding on transgenic tobacco with 2 indigenous insect species commonly associated with wild and commercial tobacco involving plants grown and evaluated under laboratory and field conditions. The highest levels of PFA ranged from 1.3 to 2.7 g/kg leaf fresh weight produced in the field-grown cultivars Con Havana and Little Crittenden, respectively. These two cultivars also had the highest nicotine (ranging from 4.6 to 10.9 mg/g), but there was little to no negative effect for either tobacco hornworm Manduca sexta L. or aphid Myzus nicotianae (Blackman). Both laboratory and field trials determined no short term (5 days) decrease in the survival or fecundity of the tobacco aphid after feeding on PFA transgenic tobacco compared to non-transgenic plants. In the field, tobacco hornworm larvae showed no differences in survival, final larval weights or development time to adult stage between transgenic lines of four cultivars and their corresponding wild type controls. Laboratory studies confirmed the field trial results indicating the low risk association of PFA expressed in tobacco leaves with tobacco hornworms and aphids that would feed on the transgenic plants.